Syarat Regularitas dan Eulerian Graf Unit dari Ring Z_n - Kurniawan, Vika Yugi; Nisa, Lailatul Chairul (KUBIK, 2024)
Let be a ring of integers modulo and denote the set of all unit elements of the ring. The unit graph of which is denoted by is a simple graph, where the vertices of are all elements of, where two different vertices and are connected by an edge if and only if is the unit of. In this article, we will examine the properties of the unit graph of the ring. The results of this study show that is an Euler graph if where is even, and is a regular graph if is even.